Analysis of Bankruptcy Predictions Due to Boycott at PT. Unilever using The Altman Z-Score, Zmijewski X-Score, Fulmer, and Taffler Methods. - Suhadi, Agus; Mubarak, Husni (LPPM ISNJ Bengkalis, 2025)
This research aims to evaluate and project the risk of bankruptcy of PT. Unilever Indonesia due to financial difficulties caused by the boycott. The method used is quantitative descriptive by applying four bankruptcy prediction models Altman Z-Score, Zmijewski X-Score, Fulmer, and Taffler to analyze the company's financial condition during the 2019-2023 period. The results of the study show that based on the four methods, the company is in a condition of non-distress. Although there are different approaches in each model, the results still show a trend of deteriorating corporate financial health. In conclusion, although each prediction model uses a different method of analysis, these findings remain an important signal for companies to understand the state of their financial health in more depth.